T1-weighted Grey Matter Signal Intensity Alterations After Multiple Administrations of Gadobutrol in Patients with Multiple Sclerosis, Referenced to White Matter. Issue 1 (December 2018) - Kelemen, Peter; Alaoui, Jamila; Sieron, Dominik; Chan, Andrew; Kamm, Christian; Heldner, Mirjam; Gralla, Jan; Wiest, Roland; Verma, Rajeev
Abstract The aim of the study was to investigate the signal-intensity-(SI)-ratio changes in the basal ganglia, the pulvinar thalami (PN), and the dentate nucleus (DN) using frontal white matter (FWM) as reference area, in patients with multiple sclerosis after frequent administrations of gadobutrol. A control group (group I) was compared to three stratified patient groups (group II: mean applications of gadobutrol 3.7; group III: 7.5 applications; group IV: 13.8 applications). SI-ratios of the pallidum, putamen, caudate nucleus, and pulvinar thalami were calculated with: 1. FWM, and 2. PN. DN-to-pons and DN-to-FWM ratios were also calculated. The most significant SI-ratio-changes were found by comparing group I and IV for both reference values. However, by using FWM as reference an SI-ratio increase was observed, while an SI-ratio decrease was seen if referenced to the PN. DN-to-FWM showed an SI-ratio increase, too. The PN revealed a significant SI-ratio increase itself, correlating with the number of gadolinium applications, when referenced to FWM. Therefore, SI-ratio calculations using the thalamus as reference might be flawed. In addition, a minor gadolinium accumulation is possible, if FWM was used as reference area. Further studies are necessary to verify our results.